2010
DOI: 10.1021/ic9014064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Binuclear Copper(II) Complexes for Glycoside Hydrolysis

Abstract: Three binuclear copper(II) complexes were characterized as solids by X-ray diffraction and in solution by UV/vis spectrophotometric titration, and subsequently evaluated for their glycosidase-like activity. The structure analysis revealed comparable intermetallic Cu...Cu distances (approximately 3.5 A) for the complexes 2 and 3. Despite this similarity, the composition of the complexes differs significantly in aqueous solution as revealed by spectrophotometric titrations. The hydrolysis of selected nitrophenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
73
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(75 citation statements)
references
References 45 publications
2
73
0
Order By: Relevance
“…These studies involve proteins with heme groups, [134][135][136] Zn-nger motifs, [137][138][139] metalloproteins 116,133,[140][141][142] and/or other complexing agents in solution. 81,[143][144][145] In fact, the concentrations of the compounds used, and most importantly the ratio of the buffer concentration to the complexing compound concentration in the medium, are within values that support the idea that no interference of the buffer occurs.…”
Section: Hepesmentioning
confidence: 67%
See 1 more Smart Citation
“…These studies involve proteins with heme groups, [134][135][136] Zn-nger motifs, [137][138][139] metalloproteins 116,133,[140][141][142] and/or other complexing agents in solution. 81,[143][144][145] In fact, the concentrations of the compounds used, and most importantly the ratio of the buffer concentration to the complexing compound concentration in the medium, are within values that support the idea that no interference of the buffer occurs.…”
Section: Hepesmentioning
confidence: 67%
“…Table 2 presents examples of the applications of Good's buffers, such as in biomolecular, biochemical, molecular and cellular biology, toxicology and environment studies, where a wide array of techniques, such as chromatography, 71-74 electrophoresis, 75-78 spectrophotometry 79-81 and X-ray crystallography 81,82 were used.…”
Section: Employment Of Good's Buffers In Biochemical Biological and mentioning
confidence: 99%
“…[16] The hydrochlorides of S -4 and R -4 were obtained after reduction of 6 with borane in THF and treatment of the reaction products with hydrogen chloride in absolute ethanol. [17] In analogy to the synthesis of bpdpo described above,[18] condensation of the free diaminoalcohols with pyridinecarbaldehyde afforded the chiral ligands S -bpdbo ( S -7 ), and R -bpdbo ( R -7 ), respectively, after reduction of the initially formed Schiff bases with sodium borohydride in methanol. Enantiopure binuclear copper(II) complexes S - 2 and R - 2 were prepared from the pentadentate ligands 7 and copper(II) acetate in methanol following our synthetic protocols for the synthesis of complex 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Enantiopure binuclear copper(II) complexes S - 2 and R - 2 were prepared from the pentadentate ligands 7 and copper(II) acetate in methanol following our synthetic protocols for the synthesis of complex 2 . [18] Caution : Perchlorate salts are potentially explosive. However, we did not experience any difficulty in handling or drying the complexes below 50 °C.…”
Section: Resultsmentioning
confidence: 99%
“…The long-term goal of the authors is to use the developed catalyst to selectively form glycosidic bonds by transglycosylation. Data presented in a previous paper (published a year earlier [33]) showed that the hydrolysis of p-nitrophenyl-α-D-galactopyranoside can be accelerated 11,000 times over the background reaction when binuclear complex Cu 2 (bpdpo)(OAc) is used as catalyst; however, despite the high rate of acceleration, significant product inhibition limits its application. In order to increase the rate of the reaction even more and to avoid product inhibition, the metal complex was anchored on a polymeric matrix.…”
Section: Hydrolytic Reactions On Challenging Substratesmentioning
confidence: 99%